NATURALLY OCCURING BOTANICAL EXTRACTS FOR THE MANAGEMENT OF STORAGE WEEVIL INFESTATION: A REVIEW - Usman, D. A.; Ahmed H.; Babura, S. R. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
Post-harvest grain losses caused by storage weevils remain a major constraint to food security in many developing countries. Species of Sitophilus, particularly S. oryzae, S. zeamais, and S. linearis, inflict extensive damage during storage due to their concealed larval development, rapid reproductive cycles, and strong adaptation to storage environments. The limitations and health concerns associated with synthetic insecticides have stimulated renewed interest in plant-derived pest management. This review synthesizes current knowledge on the biology and ecology of storage weevils, the phytochemical basis of botanical insecticides and the efficacy of plant extracts in grain protection. Key phytochemicals including alkaloids, terpenoids, phenolics, and Saponins were identified. Their diverse mechanism includes insecticidal, repellent, fumigant, and growth-inhibitory regulation and synergistic enhancement. Botanicals such as Azadirachta indica, Ocimum basilicum, Zingiber officinale, Curcuma longa, Allium sativum, and Eucalyptus spp. demonstrate significant activity against Sitophilus species, with effectiveness influenced by extraction solvent, concentration, and exposure duration. While plant-based pesticides offer safe, environmentally compatible alternatives to chemical insecticides. Overall, botanical extracts hold strong potential for sustainable, integrated management of storage weevils and improved post-harvest grain security.